Thomas Betterton's Book-Trade Apprenticeship and the Amazing Careers of His Two Masters, John Holden and John Rhodes, with Some Notes on the Actor's Library. (23rd December 2022) - Ferdinand, Christine
Abstract: Thomas Betterton has been described as 'the greatest English actor between Burbage and Garrick' as well 'the pre-eminent manager of his time' (ODNB) ; yet he began his career in the book trade, with an informal apprenticeship split between entirely different masters. The first was the ambitious John Holden who might have succeeded Humphrey Moseley as the most important literary publisher of the day, had he not died young. His second master was John Rhodes, who took a more pragmatic view of bookselling. Rhodes' heart was in the theatre—he briefly had his own company and purchased shares in a playhouse—but he understood that bookselling provided a more stable income. Rhodes would have kept the young Betterton busy in his bookshop, but he probably also gave Betterton his first stage experience. While Betterton went on to a brilliant acting and managing career, he continued his association with books, accumulating a large working library.